Last best hope : America in crisis and renewal - Packer, George, 1960- (New York : Farrar, Straus and Giroux, 2021)
"Acclaimed National Book Award-winning author George Packer diagnoses America's descent into a failed state and envisions a path toward overcoming our injustices, paralyzes, and divides"--
HB